ANALGETIC POWER OF ETHANOL EXTRACT BROTOWALI (TINOSPORA CORDIFOLIA) IN SWISS MICE - Deni Firmansyah; Didin Ahidin; Sulistiorini Indriaty; Siti Nurhasanah; Nahdia Fajri Mahmudah; Titin Sumarni (Universitas Muhammadiyah Magelang, 2022)
Brotowali (Tinospora cordifolia) plants are usually used for various kinds of treatment it is often used as a febrifuge, brotowali stems are proven to contain flavonoid compounds that have benefits in the treatment of various diseases, one of which is analgesic. This purpose is to determine the effectiveness of analgesics on male Swiss mice induced by acetic acid from the ethanol extract of brotowali stem (EETC) doses of 100 mg/Kg BW, 200 mg/Kg BW, and 400 mg/Kg BW. Brotowali stem extraction using maceration method with 70% ethanol solvent. EETC was tested by phytochemical screening and TLC to determine the content of active compounds. The test animals used Swiss male mice, the treatment group was divided into 5, negative control group, positive control, and the dose groups were 100 mg/kg BW, 200 mg/kg BW, and 400 mg/kg BW. Testing is done by the writhing test method. Induction of pain stimuli using acetic acid, the number of mice writhing every 10 minutes for 1 hour, and the percentage of analgesic power. Research shows the yield of EETC is 16.35%. The percentage of analgetic power of dose I was 39%, dose II was 47% and dose III was 56% less than the percentage of analgesic power of methampyrone dose of 65 mg/KgBB which was 64%. Conclusion EETC doses of 100 mg/kg BW, 200 mg/kg BW, and 400 mg/kg BW have analgesic activity equivalent to methampyrone at a dose of 65 mg/kg BW, with the largest percentage of analgesic protection at a dose of 400 mg/Kg BW of 56%.